Dampak konsumsi susu kambing terhadap anthropometri, tekanan darah, kekuatan otot tungkai dan kalsium pada pesepakbola junior - Yusni Yusni; Amiruddin Amiruddin (AcTion: Aceh Nutrition Journal, 2021)
Goat milk contains beneficial nutrients that supposedly improve the performance and health of athletes. The objective of this research was to discover the benefits of goat milk on anthropometric (weight, height, body mass index (BMI)), blood pressure (BP), leg muscle strength (LMS), and calcium in junior footballers. This research was a quasi-experimental design (one group pretest-posttest). Subjects: 22 football athletes, male, 12-16 years old, regular training, and healthy. The sampling technique was purposive sampling. The treatment was fresh goat's milk, a dose of 250 ml/day, given at 04.00-06.00 p.m, throughout 21 days. The subject examination includes measurements: weight, height, BMI, BP, LMS, and serum calcium using a weighing scale, microtoise, BMI formula, sphygmomanometer and stethoscope, leg dynamometer, and Cresol Phtalein Complex. Data were analyzed by paired sample t-test (p<0,05). Results, there were significant differences in weight (p= 0,000) and BMI (p= 0,033) before and after treatment. Conversely, there was a significant enhancement of LMS (p= 0,000), systolic (p= 0,005), without a diastolic increase (p= 0,143), significantly decreased hypocalcemia percentage (p= 0,001) after treatment. In conclusion, consumption of fresh goat milk regularly increased LMS, regulates diastolic within normal limits, as well as reduces weight, BMI, and percentage of hypocalcemia therefore it is highly recommended to consume 2-3 glasses of goats milk per day for junior footballers.